2003
DOI: 10.1902/jop.2003.74.10.1440
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Stimulates Osteoclast Resorption in a Porcine Marrow Cell Model

Abstract: Nicotine is non-toxic to osteoclasts at the clinically relevant levels tested. Nicotine appears to stimulate osteoclast differentiation and resorption of calcium phosphate, the major component of bone. Nicotine-modulated osteoclast stimulation may, in part, explain the increased rapidity of periodontal bone loss and refractory disease incidence in smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0
14

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 38 publications
6
46
0
14
Order By: Relevance
“…Er et al [13] found that fibroblast metabolism could be altered by nicotine action and intercellular matrix synthesis was affected. It also affects periodontal ligament fibroblasts and stimulates osteoclasts activity [19,42]. In our study, nicotine administration caused a change in fibroblast activity due to the change of collagene fiber synthesis and decreased MMP2 expression.…”
Section: Discussionsupporting
confidence: 51%
“…Er et al [13] found that fibroblast metabolism could be altered by nicotine action and intercellular matrix synthesis was affected. It also affects periodontal ligament fibroblasts and stimulates osteoclasts activity [19,42]. In our study, nicotine administration caused a change in fibroblast activity due to the change of collagene fiber synthesis and decreased MMP2 expression.…”
Section: Discussionsupporting
confidence: 51%
“…It also affects periodontal ligament fibroblasts (Pinto et al, 2002) and stimulates osteoclasts activity (Yuhara et al;Henemyre et al, 2003). The group treated with nicotine, cement and vimentin expression was observed in the periodontal membrane density irregularities along the collagen fibers were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies reported that nicotine stimulated the formation and differentiation of osteoclasts, 7,8 suppressed osteogenesis in osteoblasts, directly stimulated osteoclast precursors, and induced an imbalance of osteoblasts and osteoclasts in vitro. 9, 10 Rothem et al 11 suggested that nicotine affected osteoblast cell proliferation in a biphasic manner, including toxic and antiproliferative effects at high levels of nicotine and stimulatory effects at low levels.…”
Section: Introductionmentioning
confidence: 95%